Identification of determinants for technology-based venture creation and growth in Malaysia / Nazatul Shima Abdul Rani - Abdul Rani, Nazatul Shima (2008)
In Malaysia, since there were much emphasis being put forth on topics of technology-based venture and technopreneurship, one would expect it to have a rich tradition of theory development, scale development, and empirical research. However, in the case of technology-based venture this is partially true. To date, much of the studies related to technologybased venture focused on technology transfer, technology adoption, incubator program, innovation and venture capitalist (Lee, 2002; Freel, 2000; Camp & Sexton, 1992). There is a need to study the determinants for technology-based venture creation and growth in Malaysia, in order to ensure that the development and growth of those businesses will not be halted. This study is important to be conducted in Malaysia because technology-based venture plays an important role as an economic engine by creating more jobs and wealth in Malaysia. The main research problem is to find answer for the following: "What are the important determinants for technology-based venture creation and growth for Malaysian SMEs?' The population samples were drawn from database of small and medium industries in Malaysia provided by SMIDEC. The database comprises of 5,000 over technology-based venture and nontechnology based venture in Malaysia. A total sample of about 350 technology-based venture and 350 non-technology based venture were selected for this study and about 105 technology-based venture and 101 non-technology based venture responded to the survey that had given a response rate of 30% and 28.8% respectively. The findings of this study showed that out of six determinants identified that were business opportunity, financial resources, technology management, government support, business network and entrepreneurial drives/talents, all were found to be important at the creation stage (business opportunity, financial resources, technology management, government support, business networks and entrepreneurial drives/talents) and about 3 determinants were found to be important at the growth stage (financial resources, business networks, and government support). Thus, it showed that the determinants that were important at the creation and growth stage were identified as financial resources, business networks, and government support.